2020
DOI: 10.1029/2019jc015834
|View full text |Cite
|
Sign up to set email alerts
|

A Satellite Era Warming Hole in the Equatorial Atlantic Ocean

Abstract: Observations during the satellite era 1979-2018 only depict small sea surface temperature (SST) trends over the Equatorial Atlantic cold tongue region in boreal summer. This lack of surface warming of the cold tongue, termed warming hole here, denotes an 11% amplification of the mean SST annual cycle. The warming hole is driven by a shoaling of the equatorial thermocline, linked to increased wind stress forcing, and damped by the surface turbulent heat fluxes. The satellite era warming deficit is not unusual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…However, multidecadal variability is large. Nnamchi et al (2020) found that SSTs during the satellite era 1979-2018 exhibit a warming hole over the equatorial Atlantic cold tongue region in boreal summer. This lack of surface warming denotes an 11% amplification of the mean SST annual cycle in that region.…”
Section: Introductionmentioning
confidence: 99%
“…However, multidecadal variability is large. Nnamchi et al (2020) found that SSTs during the satellite era 1979-2018 exhibit a warming hole over the equatorial Atlantic cold tongue region in boreal summer. This lack of surface warming denotes an 11% amplification of the mean SST annual cycle in that region.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above (Sect. 1), WEA wind changes could affect the D20 through equatorial waves and lead to SST changes in the EACT region (Planton et al 2018;Marin et al 2009;Nnamchi et al 2020). Under RCP8.5, we analyze the correlation between wind changes in the WEA and D20 changes and found that there is a weak correlation (r = 0.38 not significantly at the 95% significance level) between these two terms (Fig.…”
Section: Changes In the Sst Of Eact And Their Driversmentioning
confidence: 99%
“…An intensification of winds in the WEA could induce upwelling Kelvin waves that propagate eastward and trigger the rising of the thermocline (represented by the 20 °C isotherm or D20) to the East, and vice versa for a weakening of winds (e.g., Castaño-Tierno et al 2018). This movement of the thermocline leads to a reduction (augmentation) in the sea surface height (SSH) and SST in the EACT region (Planton et al 2018;Marin et al 2009;Nnamchi et al 2020). Thus, as the EACT region is largely related to the West African summer monsoon precipitation which is of key importance for agriculture productivity and water availability, it is essential to study the changes of SST under GLENS in this region.…”
Section: Introductionmentioning
confidence: 99%
“…These processes can also affect the interannual variability (Prodhomme et al, 2019) and affect the uncertainty of the simulated climate change signal (Tokinaga and Xie, 2011;Nnamchi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%